Intervention Academic Stress in Adolescents - I Gusti Ayu Setia Maha Yuni; Ni Made Ari Wilani (Psikostudia : Jurnal Psikologi, 2025)
Academic stress in adolescents often affects their emotional and cognitive well-being, which can interfere with academic achievement and quality of life. This study aims to explore interventions that can reduce academic stress in adolescents with an approach based on stress management techniques and social support. The method used is a literature study that reviews various studies on academic stress in adolescents and effective intervention strategies. Based on the literature, relaxation techniques, time management, and social support from family and school have been shown to reduce academic stress in adolescents. In conclusion, an integrated intervention approach between psychological skills and environmental support is very important to overcome academic stress in adolescents. Stres akademik pada remaja sering kali mempengaruhi kesejahteraan emosional dan kognitif mereka, yang dapat mengganggu prestasi akademik serta kualitas hidup. Penelitian ini bertujuan untuk mengeksplorasi intervensi yang dapat mengurangi stres akademik pada remaja dengan pendekatan yang berbasis pada teknik manajemen stres dan dukungan sosial. Metode yang digunakan adalah studi literatur yang meninjau berbagai penelitian mengenai stres akademik pada remaja serta strategi intervensi yang efektif. Berdasarkan literatur, teknik relaksasi, pengelolaan waktu, dan dukungan sosial dari keluarga dan sekolah terbukti dapat mengurangi stres akademik remaja. Kesimpulannya, pendekatan intervensi yang terintegrasi antara keterampilan psikologis dan dukungan lingkungan sekitar sangat penting untuk mengatasi stres akademik pada remaja.